REVIEW OF IDENTIFIED SHORTCOMINGS IN AQUIFER VULNERABILITY ASSESSMENTS - Anthony Okeh; Abu Mallam; Osagie Abel Uyimwen; S. A. Ganiyu (Journal CleanWAS)
Several studies have successfully carried out aquifer vulnerability evaluations using a combination of geophysical and biogeochemical methods. Unfortunately, some identified shortcomings have often led to inaccurate assessments. This review attempts to identify some of these drawbacks and suggest better ways to improve upon analysis and interpretation of results. Articles reviewed were sourced publicly and subjected to systematic analysis based on fundamental principles. The outcomes of each analysis were discussed, among which was a study that applied Ohmega Resistivity meter to acquire Self-Potential (SP) data without specifying the nature of electrode used. The result indicated large SP readings ≥200mV attributed to high fluid flow. According to analysis, when copper stakes are used, spurious SP readings occur in contrast to lower SP values of roughly 10 mV when suitable non-polarizable electrodes of Cu/CuSO4 porous pots are utilized to collect SP data. The review made clear the importance of providing detailed explanation of the nature of materials used. Another study solely collected samples for groundwater quality assessments during dry season, ignoring the effects of seasonal variation on water parameters. This must have had an impact on the results of the investigations. Research examined the aquifer problems in Gosa area of Abuja, utilizing only the Vertical Electrical Sounding (VES) technique. The study suggested basaltic intrusion as probable cause of borehole failures in the area. A different research which incorporated VES and data from the hill-shaded Shuttle Radar Topography Mission (SRTM), suggested insufficient interconnectivity within the fractures as conditions controlling groundwater occurrence in the area. The study illustrated the need for integrating geophysical methods for effective target detection. To map the infiltration of leachate into the subsurface, a study applied only the VES technique. Studies, however, showed that the VES method only provided average resistivity readings, suppressing some features. The study suggested the combination of VES and 2-D imaging for more accurate results. Another study obtained data via the ADMT Groundwater Detector. At the interpretation stage, the author interpreted ADMT data as VES, which was perceived as inaccurate as their principles and methodologies are different. Another study was noted to have presented results without categorizing the Aquifer Protective Capacity (APC) rating in percentages (%). It was assessed that a framework that accurately categorized the APC of each transversal using common statistics guidelines would have made it simpler to understand and aided decision-making. Future research is advised to take some of the noted flaws into account in order to enhance data processing and interpretation.